Architecture of the Northern Macedonia after Reinstallation of the Byzantine Rule - Maltseva, Svetlana V.; Freze, Anna A. (Actual Problems of Theory and History of Art, 2021)
Architectural landscape of the Northern Macedonia after reinstallation of the Byzantine jurisdiction in no way may be called homogenous. The monuments are characterized by diverse approaches to the form, construction, technology and style. All of them have different ratios of “provincial” and “metropolitan” architectural features. Nonetheless, the extant monuments, their architectural allusions to the Constantinopolitan architecture and their history available to us testifies to the importance of the Macedonian theme for the Byzantine Empire. Primary evidence is given by the large building projects renewing religious centres –— bishoprics of Vodoća and Morodviz, archbishopric of Ohrid. Monasteries, founded, by the members of the imperial family of the Komnenoi, prove the vital interest of the Byzantine aristocratic circles in the Northern Macedonia.This research has been completed with the support of the Russian Science Foundation (RSF), project № 20-18-00294.
Keywords: Northern Macedonia; Byzantine architecture